Fatigue behaviour of AISI 304 steel to AISI 4340 steel welded by friction welding - Hascalik, A.; Unal, E.; Ozdemir, N. (Springer, 2006)
In the presented study, The weldability of AISI 304 austenitic stainless steel to AISI 4340 steel joined by friction welding in different rotational speeds and fatigue behaviour of friction-welded samples were investigated. Tension tests were applied to welded parts to obtain the strength of the joints. The welding zones were examined by scanning electron microscopy (SEM) and analyzed by energy dispersive spectroscopy (EDS). The Vickers microhardness distributions in welding zone were determined. Fatigue tests were performed using a rotational bending fatigue test machine and the fatigue strength has been analysed drawing S-N curves and critically observing fatigue fracture surfaces of the tested samples. The experimental results indicate that mechanical properties and microstructural features are affected significantly by rotation speed and the fatigue strength of friction-welded samples decrease due to chromium carbide precipitation in welding zone with increasing rotation speed in choosen conditions. (c) 2006 Springer Science + Business Media, Inc.
Keywords: Stainless-Steel; Ti-6Al-4V Alloy; Crack Growth; Resistance; Interface; Corrosion; Copper